Copy Number Heterogeneity in the Virulence Plasmid of Salmonella enterica - Sánchez-Romero, María A.; Mérida-Floriano, Ángela; Casadesús, Josep (Frontiers in Microbiology, 2020)
Quantitative PCR analysis shows that the virulence plasmid of Salmonella enterica serovar Typhimurium (pSLT) is a low-copy-number plasmid, with 1-2 copies per chromosome. However, fluorescence microscopy observation of pSLT labeled with a lacO fluorescent tag reveals cell-to-cell differences in the number of foci, which ranges from 1 to 8. As each focus must correspond to ≥1 plasmid copy, the number of foci can be expected to indicate the minimal number of pSLT copies per cell. A correlation is found between the number of foci and the bacterial cell volume. In contrast, heterogeneity in the number of loci appears to be independent of the cell volume and may have stochastic origin. As a consequence of copy number heterogeneity, expression of a pSLT-bone reporter gene shows high levels of cell-to-cell variation, especially in actively dividing cultures. These observations support the notion that low-copy-number plasmids can be a source of gene expression noise in bacterial populations.